2002
DOI: 10.1590/s1517-86922002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Perfil psicológico de atletas paraolímpicos brasileiros

Abstract: O objetivo deste estudo é apresentar e discutir os resultados da preparação psicológica realizada com 64 atletas de oito diferentes esportes. A avaliação foi realizada nos Centros de Treinamento Paraolímpicos no Rio de Janeiro, São Paulo e Recife. Foram aplicados testes de personalidade, testes de motivação, questionário de estresse e testes psicométricos (percepção, concentração e tempo de reação). Foi detectada diferença significativa em alguns parâmetros psicológicos ao comparar os atletas de acordo com o s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 0 publications
0
8
0
24
Order By: Relevance
“…The results showed that four weeks of forced PE on a treadmill significantly increased central locomotion in the OF and open arm entries in the EPM for both strains compared with their respective SED controls, indicating an anxiolytic-like effect of forced PE. In humans, PE has been shown to decrease anxiety and depression levels and improve physical well-being (McKercher et al, 2009;Samulski et al, 2009;Unesco, 2013). Some studies also suggest that PE could be used as a treatment for anxiety and depression (Ströhle, 2009).…”
Section: 3 Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that four weeks of forced PE on a treadmill significantly increased central locomotion in the OF and open arm entries in the EPM for both strains compared with their respective SED controls, indicating an anxiolytic-like effect of forced PE. In humans, PE has been shown to decrease anxiety and depression levels and improve physical well-being (McKercher et al, 2009;Samulski et al, 2009;Unesco, 2013). Some studies also suggest that PE could be used as a treatment for anxiety and depression (Ströhle, 2009).…”
Section: 3 Statistical Analysismentioning
confidence: 99%
“…Introduction A growing body of evidence indicates the positive influence that lifestyle factors, including physical exercise (PE), social interaction and nutrition, can have on emotionality in humans (Kramer et al, 1985;Fox, 1999;Ratey & Loehr, 2011;Hötting & Röder, 2013). For example, periodic PE decreases anxiety, improves mood, physical well-being and mental disposition (McKercher et al, 2009;Samulski et al, 2009;UNESCO, 2013). It also may have a positive influence on the modulation of brain neurotransmitter systems , related to improvements in cardiovascular function (Murlasits, 2015;Dunn et al, 2005), and increases brain plasticity and resilience to stress, which could prevent the development of mental disorders .…”
mentioning
confidence: 99%
“…Em seguida, foi feita a análise de variância e pós-teste de comparação de Tukey. Quanto a isto, Samulski (2002) coloca que a raiva se manifesta quando se tem uma meta que foi perdida por não ter havido esforço suficiente, ou se não puder ser alcançada mesmo com muito esforço. Pode se dizer que a origem da raiva tem por base o fracasso e o não cumprimento das expectativas, que se supunham segura, mas que não foram concretizadas.…”
Section: Análise De Dadosunclassified
“…Segundo Samulski (2002), em uma competição, o esportista se encontra em um estado de estresse psíquico, que para alguns autores tem sido denominado estado pré-competitivo. Esse estado se caracteriza, sobre o ponto de vista psicológico, pela antecipação das oportunidades, riscos e conseqüências.…”
Section: Introductionunclassified
“…Cada vez mais o esporte paralímpico tem ocupado espaço no cenário nacional e mundial (SAMUL-SKI;NOCE, 2002;ANJOS;PARREIRAS, 2006;GREGUOL et al, 2011). Ademais, conforme Bracht et al (2011), estudos norteados pela finalidade de apresentar um apanhado sobre a produção científica de campos investigativos emergentes, são necessários, uma vez que, auxiliam na reflexão e norteiam a própria constituição destes recentes contextos de produção.…”
Section: Introductionunclassified